Dynamics of Culture and Visual Profiling - Agwuele, Augustine (The Symbolism and Communicative Contents of Dreadlocks in Yorubaland, 2016)
According to Goodenough, “It is the forms of things that people have in mind, their models for perceiving, relating and otherwise interpreting them.” This work has been primarily focused on the description and explanation of Yoruba thought processes, specifically focusing on their long-sustained core belief system and worldview, which prominently influence their perception of deviant hairstyles. In doing so, it has relied on the manifest behaviors from different contexts of interactions, suggesting connections between “trivial” displays and layered societal cosmology. The approach is based on the assumption that the entire cultural system of a society is best understood by studying symbols, especially their constitutive power, through which the system is not only structured but also motivated. Thus, the symbolism of (normative, as well as deviant) hairstyle is related to sociocultural structures, including, at its base, a cosmologically informed worldview, that is, a people’s view of the way things actually are, as well as their concepts of nature, self, society. Sign is anything that stands for something else; words, objects, and gestures are also signifying elements. The arbitrariness of the relationship between sign and what is signified ensures that the relationship receives peculiar interpretation across cultures. According to Peirce, there are three different types of non-exclusive signs: iconic signs resemble what is represented directly, indexical signs imply the signified and directly connect to other experiences, and symbolic signs offer an arbitrary relationship. Aye is reified in dreadlocks, whereas nefarious activities are indexed by dreadlocks. Yoruba males who wear these hairstyles violate social order, subvert gender roles, and transgress against established norms and mores. Thus, they are the very symbol of the diabolical, walking around in search of whom to destroy.